The (100), (111) and (110) surfaces of diamond: an ab initio B3LYP study - De La Pierre, Marco; Bruno, M.; Manfredotti, C.; Nestola, F.; Prencipe, M.; Manfredotti, C. (Taylor & Francis, 2014)
We present an accurate ab initio study of the structure and surface energy of the low-index (100),(111) and (110) diamond faces, by using the hybrid Hartree-Fock/Density Functional B3LYPHamiltonian and a localized all-electron Gaussian-type basis set. A 2D periodic slab model has been adopted, for which convergence on both structural and energetic parameters has been thoroughly investigated. For all the three surfaces, possible relaxations and reconstructions have been considered; a detailed geometrical characterization is provided for the most stable structure of each orientation. Surface energy is discussed for all the investigated faces.